POWER, PERSUASION, AND CONSUMER IDENTITY: A CRITICAL DISCOURSE ANALYSIS OF MCDONALD’S ADVERTISEMENT CALLED ‘SELF-CONTROL, WHO?’ - Amzelina Risty Br. Lubis, Aliffa; Jayanti; Izhar Maulana, Alif; Zein, T. Thyrhaya (Department of English Education, Universitas Panca Sakti Bekasi, 2024)
The purpose of this research is to analyze power, persuasion, and consumer identity McDonald's advertisements in terms of critical discourse analysis techniques. Research focus on persuasiveness has been popular for a long time, studied as the art of speaking and features of rhetoric. Linguists have never stopped in their quest to find out what linguistic elements create persuasive effects and impact human brains to convince people about something. The research aimed by applying CDA to this advertisement, research seeks to uncover how McDonald's uses discourse as a tool for ideological persuasion and how it constructs a consumer identity aligned with contemporary values of individualism and freedom of choice. This study adopts a qualitative research design to analyze McDonald’s